2018
DOI: 10.1002/art.40500
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐25 Axis Is Involved in the Pathogenesis of Human Primary and Experimental Murine Sjögren's Syndrome

Abstract: IL-25 may promote the inflammatory state in primary SS and may be a potential target for novel disease-modifying therapeutic strategies in patients with primary SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…IL‐25 has been only reported in pSS at the local level: high mRNA expression in LSG biopsy, and it had been related to inducing type 2 innate lymphoid cells. The precise effect at the systemic level is unknown 11 . Nevertheless, IL‐25 levels presented a median value than was not exceed to 1 pg/mL in both groups (pSS: 0.5 pg/mL and CS: 0.009 pg/mL), and these levels should be taken carefully.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…IL‐25 has been only reported in pSS at the local level: high mRNA expression in LSG biopsy, and it had been related to inducing type 2 innate lymphoid cells. The precise effect at the systemic level is unknown 11 . Nevertheless, IL‐25 levels presented a median value than was not exceed to 1 pg/mL in both groups (pSS: 0.5 pg/mL and CS: 0.009 pg/mL), and these levels should be taken carefully.…”
Section: Discussionmentioning
confidence: 94%
“…About inductors and maintainers of Th2 response, IL‐33 was identified at glandular and soluble expression without clinical association in pSS 9,10 . Moreover, high IL‐25 mRNA expression from LSG associated with the lymphocytic infiltration was reported 11 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, IL-17E/IL-17RB interaction can promote Th2 responses, regulate B cell function, and induce Th17driven autoimmune inflammation (25). In SS patients, it was reported to participate in pathogenesis by promoting inflammation (26). Thus, we speculated that anti-IL-17RB antibodies may act as agonist of IL-17RB and play a potentially similar proinflammatory role in TAK patients.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous studies have demonstrated that Th17 cells are important in initiating the pathogenesis of SS, indicating a key role for IL-17A in SS (7) provokes inflammation in airways causing persistent asthma symptoms, which can be activated by IL-25. Therefore, available studies have indicated that IL-25 plays a pathogenic role during the development of SS (50,93).…”
Section: Sjö Gren's Syndromementioning
confidence: 99%